Does Statin or ASA Affect Survival When Prostate Cancer Is Treated with External Beam Radiation Therapy? - J. Caon; M. Paquette; J. Hamm; T. Pickles (Prostate Cancer)
Background. Prior studies evaluating the effect of statins or acetylsalicylic acid (ASA) on the survival of men receiving prostate cancer were treatment have reported conflicting results, and have not adjusted for comorbidity. Our aim is to investigate the influence of statins and ASA on prostate cancer survival, when comorbidity is adjusted for, in men treated with external beam radiation therapy (EBRT) for prostate cancer. Methods. A cohort of 3851 patients with prostate cancer treated with curative EBRT ± androgen deprivation therapy (ADT) between 2000 and 2007. Stage, treatment, medication use, and Charlson comorbidity index (CCI) scores were analyzed. Results. Median followup was 8.4 years. Mean age was 70.3 years. Neoadjuvant ADT was used in 67%. Statins were used in 23%, ASA in 24%, and both in 11%. Comorbidity scores were 0 in 65%, 1 in 25%, and ≥2 in 10% of patients. Statin and ASA use were associated with increased age and comorbidity. Although statin and ASA use were significantly associated with improved prostate cancer specific survival (PCSS) on univariate analysis, neither were on multivariate analysis. Conclusion. Neither statin nor ASA use impacted PCSS on multivariate competing risks analysis. Survival was impacted by increased comorbidity as well as statin and ASA use.